2012
DOI: 10.1093/cid/cis751
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Vitamin D Status to Prognostic Scores Improves the Prediction of Outcome in Community-Acquired Pneumonia

Abstract: NCT00471640.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 34 publications
1
50
1
3
Order By: Relevance
“…One of the most frequently studied infections with respect to vitamin D deficiency is CAP. Increased mortality in CAP was found to be related to vitamin D deficiency [13,14]. There are also growing data about vitamin D status on the prediction of outcomes in CAP, sepsis, and critically ill patients [24,25,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequently studied infections with respect to vitamin D deficiency is CAP. Increased mortality in CAP was found to be related to vitamin D deficiency [13,14]. There are also growing data about vitamin D status on the prediction of outcomes in CAP, sepsis, and critically ill patients [24,25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was also documented that a relationship between vitamin D deficiency and increased mortality in community-acquired pneumonia (CAP) and sepsis was found [13][14][15][16]. Despite the increasing number of studies about CAP, there are scarce data about VAP, and to our knowledge, there are no studies related to the effects of vitamin D on specific pathogens such as XDR A. baumanii in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Data from observational studies have indicated that vitamin D insufficiency is related to disease severity and prognosis [17][27] [28] but the results of our systematic review indicate that current evidence from RCTs does not support any change in practice. There is a need to conduct more placebo-controlled double blinded RCTs with adequate sample size, and appropriate dosage (discussed further below) for evaluating the safety and efficacy of vitamin D as an adjunct to antibiotics for childhood pneumonia of varying severity.…”
Section: Implications For Practice and Researchmentioning
confidence: 72%
“…In the extra-hospital population, low levels of vitamin D are positively correlated with the incidence and severity of respiratory infections [14]. In some viral infectious diseases, (e.g., influenza), low concentrations of vitamin D can be a risk factor of infection or its more severe course [15].…”
Section: Pleiotropic Action Of Vitamin Dmentioning
confidence: 99%